EFEKTIVITAS PROGRAM KELUARGA HARAPAN TERHADAP PEMBERDAYAAN MASYARAKAT DI DESA KANIE KECAMATAN MARITENGNGAE KABUPATEN SIDENRENG RAPPANG - HASTIRANI HASTIRANI; KAMARUDDIN SELLANG; LUKMAN LUKMAN (FISIP Universitas Muhammadiyah Sidenreng Rappang, 2021)
This study aims to determine the Effectiveness of the Family Hope Program on Community Empowerment in Kanie Village, Maritengngae District, Sidenreng Rappang Regency and to determine the Factors Influencing the Effectiveness of the Family Hope Program in Kanie Village, Maritengngae District, Sidenreng Rappang Regency. The population in this study were 91 Beneficiary Families of the Family Hope Program in Kanie Village where the sampling used a saturated sampling technique with the Arikunto formula, namely taking all subjects if less than 100 people, so that the sample amounted to 91 people. Data collection techniques used in this study were observation, literature review, and questionnaires. The data analysis technique used is descriptive statistics with Likert scale and frequency tables, data quality test with SPSS. The results of this study indicate that the effectiveness of the Family Hope Program on Community Empowerment in Kanie Village with a percentage value of 82% is categorized as